Development of an Interactive Picture Story E-book for Enhancing Early Childhood Sexual Knowledge - Sonita, Sandra; Utoyo, Setiyo; Rakimahwati, Rakimahwati; Nurhafizah, Nurhafizah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Because children have a limited level of sexual knowledge, teachers have not been able to use more diversified and effective technology-based learning materials to stimulate students. The purpose of this study is to evaluate the effectiveness of the interactive picture story e-book